KRAS/GNAS‐testing by highly sensitive deep targeted next generation sequencing improves the endoscopic ultrasound‐guided workup of suspected mucinous neoplasms of the pancreas. Issue 7 (16th March 2021) - Schmitz, Daniel; Kazdal, Daniel; Allgäuer, Michael; Trunk, Marcus; Vornhusen, Sylke; Nahm, Anna‐Maria; Doll, Matthias; Weingärtner, Simon; Endris, Volker; Penzel, Roland; Kirchner, Martina; Brandt, Regine; et al.
Abstract: Pancreatic cysts or dilated pancreatic ducts are often found by cross‐sectional imaging, but only mucinous lesions can become malignant. Therefore, distinction between mucinous and non‐mucinous lesions is crucial for adequate patient management. We performed a prospective study including targeted next generation sequencing (NGS) of cell‐free DNA in the diagnostic endoscopic ultrasound (EUS)‐guided workup. Pancreatic cyst(s) or main duct fluid obtained by EUS‐guided FNA was analysed by carcinoembryonic antigen (CEA), cytology and deep targeted NGS of 14 known gastrointestinal cancer genes (AKT1, BRAF, CTNNB1, EGFR, ERBB2, FBXW7, GNAS, KRAS, MAP2K1, NRAS, PIK3CA, SMAD4, TP53, APC) with a limit of detection down to variant allele frequency of 0.01%. Results were correlated to histopathology and clinical follow‐up. One hundred and thirteen patients with pancreatic cyst(s) and/or a dilated pancreatic main duct (≥5 mm) were screened. Sixty‐six patients had to be excluded, mainly due to inoperability or small cyst size (≤10 mm). Forty‐seven patients were enrolled for further analysis. A final diagnosis was available in 27 cases including 8 negative controls. In 43/47 (91.5%) of patients a KRAS‐ and/or GNAS‐mutation was diagnosed by NGS. 27.0% of the KRAS‐mutated and 10.0% of the GNAS‐mutated lesions harbored multiple mutations. KRAS/GNAS‐testing by NGS, cytology, and CEA had a sensitivity and specificity of 94.7/100%, 38.1/100%, and 42.1/75.0%, respectively. KRAS/GNAS‐testing was significantly superior to CEA ( P = .0209) and cytology ( P = .0016). In conclusion, KRAS/GNAS‐testing by deep targeted NGS is a suitable method to distinguish mucinous from non‐mucinous pancreatic lesions, suggesting its usage as a single diagnostic test. Results must be confirmed in a larger cohort.